Hijacking Transposable Elements for Saturation Mutagenesis in Fungi - Schrevens, Sanne; Sanglard, Dominique (Frontiers in Fungal Biology, 2021)
Transposable elements are present in almost all known genomes, these endogenous transposons have recently been referred to as the mobilome. These genetic units that move throughout the genome are known to affect initiation and repair of double stranded DNA breaks, genome evolution, regulatory networks, and aging. They are now increasingly used in research in order to make extensive mutant libraries in different organisms. Here we focus on their recent utilization for research in different fungal species. Fungi are an essential part of our lives on earth, they influence the availability of our food and they live inside our own bodies both as commensals and pathogenic organisms. Only few fungal species have been studied extensively, mainly due to the lack of appropriate molecular genetic tools. The use of transposon insertion libraries can however help to rapidly advance our knowledge of (conditional) essential genes, compensatory mutations and genome architecture in fungi. Here we give an overview of some recent developments in transposon mutagenesis in fungi.